Nitrogen, phosphorus, and potassium requirements to improve Sideritis cypria growth, nutrient and water use efficiency in hydroponic cultivation - Antonios Chrysargyris; Nikolaos Tzortzakis (Heliyon)
Medicinal and aromatic plant (MAP) production is gaining popularity for industrial agriculture, with phytochemical compounds having a significant impact on human health. Plant fertilization must be carefully considered as it is strongly affecting the biochemical profile of MAPs. The present study examined the Sideritis cypria responses to different nitrogen (N: 75, 150, and 300 mg/L), potassium (K: 150, 350, and 550 mg/L), and phosphorus (P: 50, 75, and 100 mg/L) concentration in the nutrient solution (NS) in hydroponics. The NPK levels (150 mg N/L; 75 mg P/L and 350 mg K/L) in the NS, which was regarded an intermediate fertilization scheme, showed a rise in nutritional value with high phenols, flavonoids and antioxidant activity in plants. S. cypria grown in N75 levels revealed a decreased plant fresh weight and chlorophylls content while plants grown in N300 levels revealed increases in mineral accumulation, nutrient and water use efficiency. The NPK and the K550 levels caused oxidative stress as demonstrated by the raised lipid peroxidation and the stimulation of enzymes’ antioxidant activities. The P50 levels in the NS, increased the plant biomass and water use efficiency (WUE) and revealed the lower oxidative stress (malondialdehyde) and increased enzymes antioxidant (superoxide dismutase and peroxidase) activities. As a result, modifying the NS composition in hydroponic culture for S. cypria by using P levels of 50 mg P/L, higher biomass, nutritive value and WUE can be obtained.